PEMBUATAN ALAT EVALUASI POLA DASA BADAN DENGAN TEKNIK DRAPING - Neuke Mora Della Munthe; As As Setiawati (Fesyen Perspektif, 2016)
Preliminary studies were conducted to know the lack of basic patterns ratings agency with the draping technique in writing but the basic pattern votes have been done based on indicators of the stage of making a basic pattern. This study aims to generate learning evaluation tool that can be used to assess the patterns of association with the draping technique. Daar pattern evaluation tool body with a draping technique such as basic patterns agency assessment format with draping techniques compiled in detail, in which there are criteria for assessment for any parts of the body with the basic pattern draping techniques. The method used in this research is the Research and Development (R D) through the preliminary study stage, making tools of evaluation, validity and revision stage. Based on the validation results show that the evaluation tools that are made can be categorized as "Eligible" with a percentage of 97.19% eligibility of subject matter experts and 100% of the expert evaluation. The results of the validation experts to the basic pattern evaluation tool body with a draping technique to agree on an evaluation tool created "Decent" is used to assess the results of the basic body pattern with the draping technique. Evaluation tool body with a basic pattern draping techniques that have been made can be the reference standard (default) in assessing the basic pattern body with draping techniques.